Shariatisation in Indonesia: A Comparative Analysis of Firanda Andirja’s and Buya Yahya’s Interpretation of Surah Al-Mā’idah 44 - Aufa Varrassyah Nawwaf; Nabiela Berliana (Bulletin of Indonesian Islamic Studies, 2025)
The idea to formalize Sharia law in Indonesia, a country characterized by its pluralism, remains the subject of ongoing debate. This discussion is fueled by diverse interpretations of Surah Al-Mā`idah 44. This article aims to analyze Firanda Andirja's interpretation as a Salafist preacher to confirm his textuality and compare it with Buya Yahya's interpretation as a non-Salafi preacher who has ties to the initiator of NKRI Bersyariah. Employing a qualitative approach alongside Norman Fairclough's discourse analysis theory, this study conducts a thorough examination of two YouTube videos that feature their interpretations. The findings indicate that their perspectives exhibit notable similarities in three main areas: both refrain from advocating for a movement to formalize Sharia, present negative portrayals of certain groups, and avoid declaring others as kāfir altogether. However, there are significant differences in how each party categorizes individuals who do not implement Sharia, as well as variations in their orientation to discourse production. Furthermore, this paper contends that Firanda's interpretation of Surah Al-Mā`idah 44 cannot be seen as purely textual, as it involves a reconsideration of the meaning of kāfir. Therefore, Abdullah Saeed’s categorization of Salafists as textualists and Quintan Wiktorowicz’s claim that Salafists avoid using rationality need to be reappraised, since these two matters may be applicable and relevant at the macro level rather than the micro level.